Realization of Structural Transformation for the Enhancement of Magnetic and Magneto Capacitance Effect in Bifeo3–Cofe2o4 Ceramics for Energy Storage Application - Casagrande-Denardin, J (Nature Research, 2021)
In this study, (1 − x) BFO-xCFO (CFO, x = 0.00, 0.05, 0.10 and 0.30) ceramics were synthesized by a solid-state reaction method; their compositions were driven by structural, microstructural, vibrational, electrical, magnetic properties; their enhanced magneto capacitance (MC) effect have also been carried out. Reitveld refinement studies of X-ray diffraction data shows composition-driven structural phase transformation from rhombohedral (R3c) to tetragonal (P4mm). Two phonon scattering Raman modes were observed for the higher wavenumber which supports the crystal structural transition in the BFO-CFO. Ferroelectric polarization shows that the polarization increased with increasing CFO concentration, which describes the changes of the polar symmetry of the crystal structure from rhombohedral (R3c) to tetragonal (P4mm). In Further, the maximum efficiency of energy density (η = 68.65%), reversible energy density of 0.138 J/cm3 and the strong magneto capacitance was observed in 0.9BFO-0.1CFO, which belongs to the morphotropic phase boundary (MPB) region near to the BiFeO3-rich region. The magnetic response analysis has shown, the saturation magnetization (Ms) values of 83 emu/gm and 139 emu/gm for pure CFO and 0.7BFO-0.3CFO composite, respectively, and their magnetic behaviours were also confirmed with Arrott–Belov–Kouvel (ABK) plot. © 2021, The Author(s).